Academic Librarians, Open Access, and The Ethics of Care - Bradley, Cara (Septentrio Conference Series, 2020)
See RECORDING (starts at 00:19:10).This presentation explores the value of applying the ethics of care to the scholarly communications work undertaken by open access/scholarly communications librarians. The ethics of care is a feminist philosophical perspective that sees in the personal a new way to approach other facets of life, including the political and the professional. Care, in this context, is broadly construed as “a species of activity that includes everything we do to maintain, contain, and repair our ‘world’ so that we can live in it as well as possible” (Fischer & Tronto, 1991, 40). Joan Tronto later went on to outline four elements of care: attentiveness, responsibility, competence, and responsiveness, and highlighted the value of care beyond the domestic sphere (1993).The ethics of care values care and relationships as instructive ways of framing and examining work, and has been applied in diverse disciplines, including education, nursing, social work, and even business. Several LIS and associated professionals have considered the ethics of care in the context of library technologies (Henry, 2016), and digital humanities (Dohe, 2019), among others. Most relevant to this presentation is the Radical Open Access Collective which, on its website, describes itself as “a community of scholar-led, not-for-profit presses, journals and other open access projects” who work to return publishing to scholars and take “back control over the means of production in order to rethink what publishing is and what it can be.” The Radical OA Collective’s inclusion of the ethics of care in their philosophy is inspirational, helping them to enact OA publishing as “a complex, multi-agential, relational practice” that shifts the focus from the neoliberal emphasis on outputs in an effort to build relationships and demonstrate care, for both individuals and communities (Deville, Moore & Nadim, 2018).After an introduction to the ethics of care, this presentation will explore the inspiration that open access and/or scholarly communications librarians might take from this perspective. What could scholarly communications librarianship learn from the ethics of care? How might our practice change or evolve with the ethics of care as an underpinning philosophy? Who do we include in our circle of care while we undertake our work? Are there other ways we can “care” or, as Fisher & Tronto propose, “maintain, contain and repair our ‘world’ so that we can live in it as well as possible”? The ethics of care provides a new way to think about our work.
Keywords: open access; scholarly communications; ethics of care